Outcomes of cochlear implants in patients with PCDH15 mutations: a clinical study - Bi, Qingling; Chen, Zhongyan; Kang, Baoling; Lv, Yong; Yuan, Yongyi; Liu, Yang; Liu, Jianfeng; Li, Yuan (Frontiers in genetics, 2025)
To explore molecular diagnoses in cochlear implantation (CI) recipients and evaluate CI outcomes in patients with mutations. Whole-exome sequencing and biomedical informatics were used to identify potential genetic causes in 467 individuals with congenital sensorineural hearing loss. We reviewed six CI recipients with mutations, assessing their CI outcomes and clinical features. Nine variants and a heterozygous variant in were identified in members of five families who underwent CI. Six of these were novel variants: exon 14-21 del, exon two del, exon 19 del, two splicing variants (c.2869-2A>C, c.1918-1G>A) in , and c.209C>T in . All but one of the individuals with mutations exhibited autosomal recessive inheritance; one showed both digenic and autosomal recessive inheritance. Variants in contributed to Usher syndrome type 1F in patients 1 and 5, whereas the remaining four had isolated deafness (DFNB23). All six patients expressed satisfaction with their CI outcomes. CI significantly improved auditory and communication abilities in individuals with mutations. Early intervention is critical for achieving favorable outcomes. Preoperative genetic testing in individuals with hearing loss provides valuable insights for predicting CI success, offering potential treatments for retinal degeneration in Usher syndrome and facilitating personalized genetic counseling.